Preparation method of high-strength ceramsite by using oil sludge-based solid waste

By mixing the residual solid phase of the sludge thermal cracking residue and the sludge chemically hot wash residue with the binder and sintered, high-strength ceramic granules are prepared, which solves the problem of fixing and resource utilization of the sludge thermal cracking residue, and realizes the solution of storage and disposal and efficient utilization of resources.

CN119859053APending Publication Date: 2025-04-22PETROCHINA CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202311366323.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing technology has failed to effectively solve the problem of fixing and resource utilization of thermal cracking residues of oil sludge, which has made it difficult to store and dispose of the reservoir.

Method used

After pretreatment of the residual solid phase of the sludge thermally cracked residue and the sludge chemically heat washing, it is mixed and mixed with the binder at a set mass ratio, granulation and aging are performed, and then preheated and sintered to obtain high-strength ceramic granules.

Benefits of technology

The fixation and resource utilization of thermal cracking residue of oil sludge is achieved, and the problem of difficulty in storage and disposal is solved, while reducing resource consumption and obtaining high-strength ceramic granules with excellent performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859053A_ABST
    Figure CN119859053A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of high-strength ceramsite by using oil sludge-based solid waste, and belongs to the field of solid waste treatment. The method comprises the following steps: respectively pretreating oil sludge thermal cracking residues and oil sludge chemical thermal washing residual solid phases; the pretreated oil sludge thermal cracking residues and the pretreated oil sludge chemical thermal washing residual solid phase are mixed, a mixture is obtained, and the mass fraction of the oil sludge thermal cracking residues in the mixture is 20%-50%; mixing the mixture with a binder according to a set mass ratio, and then performing granulation and aging to obtain raw material balls; the raw material balls are preheated and sintered, the high-strength ceramsite is obtained after cooling, the sintering temperature ranges from 1125 DEG C to 1175 DEG C, and the sintering time ranges from 10 min to 40 min; wherein the oil sludge thermal cracking residues are prepared from the following element components in percentage by mass: 30.1 percent to 52.7 percent of C, 4.9 percent to 34.6 percent of O, 7.6 percent to 29.8 percent of Si and 2.9 percent to 8.1 percent of Al. Immobilization and resource utilization of the oil sludge thermal cracking residues are achieved, and the problem that the oil sludge thermal cracking residues are difficult to stack and dispose is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solid waste treatment, and in particular to a method for preparing high-strength ceramsite using oil sludge-based solid waste. Background Art

[0002] The petroleum industry produces a large amount of oily sludge during exploration, production, transportation and processing. Different types of oily sludge have different components and are complex in composition. They are mainly composed of water and soil. They contain heavy metals, corrosive substances, sulfides, pathogens and toxic substances. If not properly handled, they will endanger the ecological environment and human health. It has been included in the "National List of Hazardous Wastes" in my country. Common industrial treatment and disposal methods include chemical hot washing, thermal cracking, incineration and cement kiln coordinated disposal, microbial in-situ remediation, etc.

[0003] Thermal cracking technology has broad development space and application prospects due to its advantages such as thorough treatment, recovery of oil and gas resources, solidification of heavy metals in sludge, and low emission of polluting gases. The oil resources that are not completely recovered from the thermal cracking products of oily sludge, as well as residual heavy metal elements and other toxic and harmful substances, are listed in the "National List of Hazardous Wastes". Because the thermal cracking is in the form of fly ash, it is very easy to spread if it is not strictly sealed and stored, and it is difficult to store. The disposal of thermal cracking residues is also one of the bottlenecks of thermal cracking technology of oily sludge. Therefore, the immobilization and resource utilization of thermal cracking residues of oily sludge are of great significance.

[0004] There are many methods for preparing ceramsite from oil sludge-based solid waste. Chinese patent CN111196731A discloses a method for obtaining porous ceramsite by mixing oil sludge dry residue, papermaking sludge and kaolin, but kaolin, potassium feldspar and other auxiliary materials still need to be added; Chinese patent CN105906176B discloses a method for preparing lightweight ceramsite by co-resource utilization of oil sludge and solid wastes such as coal gasification, coal liquefaction and kerosene co-refining residues after crushing; patent CN109305769A discloses a method for preparing building ceramsite from oil sludge and waste soil; Chinese patent CN112919879A discloses a method for obtaining a high-strength ceramsite product by adding a binder to oil sludge residue after thermochemical water washing of oil sludge and then firing; patent CN113003970A discloses a method for preparing light aggregate of oil sludge ceramsite by mixing oil sludge and activated sludge, and adding fly ash, building garbage, coal gangue and the like during the mixing process. However, none of the above inventions involve a method for immobilizing the oil sludge thermal cracking residue and a method for preparing ceramsite using the residue as a raw material, so as to achieve the purpose of immobilizing and resource utilization thereof and solve the problem of difficult storage and disposal of the oil sludge thermal cracking residue.

[0005] Therefore, it is urgent to develop a method for immobilizing and resource-utilizing oil sludge thermal cracking residue. Summary of the invention

[0006] The present application provides a method for preparing high-strength ceramsite using oil sludge-based solid waste, so as to achieve the immobilization and resource utilization of oil sludge thermal cracking residues, and solve the problem of difficult storage and disposal of oil sludge thermal cracking residues.

[0007] In a first aspect, the present application provides a method for preparing high-strength ceramsite using oil sludge-based solid waste, the method comprising:

[0008] The oil sludge thermal cracking residue and the remaining solid phase of the oil sludge chemical heat washing are pretreated respectively;

[0009] The pre-treated oil sludge thermal cracking residue and the remaining solid phase of oil sludge chemical heat washing are mixed to obtain a mixture, wherein the mass fraction of the oil sludge thermal cracking residue in the mixture is 20% to 50%;

[0010] The mixture is mixed with a binder according to a set mass ratio, and then granulated and aged to obtain raw material balls;

[0011] The raw material balls are preheated and sintered, and high-strength ceramsite is obtained after cooling, wherein the sintering temperature is 1125° C. to 1175° C., and the sintering time is 10 min to 30 min;

[0012] The oil sludge thermal cracking residue comprises the following elemental components in mass fractions: C: 30.1% to 52.7%, O: 4.9% to 34.6%, Si: 7.6% to 29.8%, and Al: 2.9% to 8.1%.

[0013] Optionally, when the mass fraction of the sludge thermal cracking residue in the mixture is 50%, the sintering process conditions include: if the sintering temperature is 1150° C., the sintering time is 30 minutes; if the sintering temperature is 1175° C., the sintering time is 20 minutes.

[0014] Optionally, when the mass fraction of the sludge thermal cracking residue in the mixture is 20%, the process conditions of the sintering include: if the sintering temperature is 1150° C., the sintering time is 20 minutes; if the sintering temperature is 1175° C., the sintering time is 10 minutes.

[0015] Optionally, the oil sludge thermal cracking residue includes the following mineral components in mass fractions: clay: 11.0% to 15.0%, quartz: 46.0% to 56.0%, potassium feldspar: 5.9% to 9.9%, plagioclase: 15.0% to 21.0%, calcite: 1.0% to 3.0%, pyrite: 0.5% to 2.5%, and amorphous: 10.2% to 18.2%.

[0016] Optionally, the remaining solid phase after chemical thermal washing of the oil sludge includes the following mineral components in mass fractions: clay: 4.7% to 7.0%, quartz: 60.9% to 68.9%, potassium feldspar: 7.9% to 12.2%, plagioclase: 15.6% to 21.0%, and calcite: 0.6% to 2.3%; the oil content of the remaining solid phase after chemical thermal washing of the oil sludge is ≤5%.

[0017] Optionally, the set mass ratio is (2-3):1.

[0018] Optionally, the preheating temperature is 350° C. to 450° C., and the preheating time is 20 min to 40 min.

[0019] Optionally, the aging method includes: drying or natural drying.

[0020] In a second aspect, the present application provides a high-strength ceramsite, which is prepared by the method described in any one of the embodiments of the first aspect, and the high-strength ceramsite includes the following mineral components in mass fractions: clay: 10.6% to 12.0%, quartz: 57.0% to 62.0%, potassium feldspar: 5.8% to 8.0%, plagioclase: 16.0% to 20.0, and hematite: 2.5% to 6.5%.

[0021] Optionally, the high-strength ceramsite meets at least one of the following properties: cylinder pressure strength ≥ 15.0 MPa, bulk density ≤ 1000 kg / m 3 The water absorption rate is 0.5% to 0.7%, and the particle diameter is 10mm to 20mm.

[0022] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0023] The present application realizes the immobilization of fly ash and heavy metals in the oil sludge thermal cracking residue. At the same time, the oil sludge thermal cracking residue and the residual solid phase of chemical heat washing are used as raw materials to prepare high-strength ceramsite, which not only solves the problem of its storage and disposal, but also realizes the resource utilization of solid waste. No additives and mineral components are required in the preparation process, which reduces the consumption of resources.

[0024] In addition, the carbon content in the pyrolysis residue in this application is relatively high, and CO or CO is generated by high-temperature reaction during the sintering process of ceramsite. 2 The gases such as argon are used to form an internal pore structure in the ceramsite, thereby reducing the bulk density of the ceramsite, controlling the amount of sludge thermal cracking residue added, the sintering temperature and the sintering time, while achieving the maximum fixed amount of cracking residue and the minimum energy consumption in the sintering process, and obtaining high-strength ceramsite with the best performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0026] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0027] Figure 1 A schematic diagram of a process for preparing high-strength ceramsite using oil sludge-based solid waste provided in an embodiment of the present application;

[0028] Figure 2 Polarized light microphotography (single polarized light 50×) of the internal flakes of the high-strength ceramsite provided in Example 1 of the present application;

[0029] Figure 3 Polarized light microscopy (single polarized light 50×) of the internal flakes of the high-strength ceramsite provided in Example 2 of the present application. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0031] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0032] In addition, in the description of the specification of the present application, the terms "including", "comprising", etc. mean "including but not limited to". In this article, relational terms such as "first" and "second", etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A and B can be singular or plural. In this article, "at least one" means one or more, and "plurality" means two or more. "At least one", "the following at least one item (items)" or similar expressions refer to any combination of these items, including any combination of single items (items) or plural items (items). For example, "at least one of a, b, or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e. a and b), ac, bc or abc, where a, b, c can be single or plural, respectively.

[0033] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0034] In the first aspect, the present application provides a method for preparing high-strength ceramsite using oil sludge-based solid waste, see Figure 1 , using typical oil sludge-based solid waste as raw materials for collaborative disposal; the method comprises:

[0035] S1, pre-treating the oil sludge thermal cracking residue and the remaining solid phase of the oil sludge chemical heat washing;

[0036] In some embodiments, the pretreatment is: grinding the raw material after drying, and passing it through a 100-mesh sieve for later use.

[0037] In some embodiments, the drying method of the raw material includes: natural drying and oven drying.

[0038] In some embodiments, the oil sludge thermal cracking residue includes the following elemental components in mass fractions: C: 30.1% to 52.7%, O: 4.9% to 34.6%, Si: 7.6% to 29.8%, and Al: 2.9% to 8.1%.

[0039] The carbon content in the pyrolysis residue is high, and it reacts at high temperature to generate CO or CO during the sintering process of ceramsite. 2The gas such as carbon dioxide and argon are added to form an internal porous structure of the ceramsite, thereby reducing the bulk density of the ceramsite. The C content can be 30.1%, 32%, 35%, 40%, 45%, 47%, 52.7%, etc., the O content can be 4.9%, 10.0%, 20.0%, 30.0%, 34.6%, etc., the Si content can be 7.6%, 10.0%, 15.0%, 20.0%, 25.0%, 29.8%, etc., and the Al content can be 2.9%, 4%, 5.0%, 6.0%, 7.0%, 8.1%, etc.

[0040] In some embodiments, the oil sludge thermal cracking residue includes the following mineral components in mass fractions: clay: 11.0% to 15.0%, quartz: 46.0% to 56.0%, potassium feldspar: 5.9% to 9.9%, plagioclase: 15.0% to 21.0%, calcite: 1.0% to 3.0%, pyrite: 0.5% to 2.5%, and amorphous: 10.2% to 18.2%.

[0041] In some embodiments, the residual solid phase of the oil sludge chemical thermal washing includes the following mineral components in mass fractions: clay: 4.7% to 7.0%, quartz: 60.9% to 68.9%, potassium feldspar: 7.9% to 12.2%, plagioclase: 15.6% to 21.0%, and calcite: 0.6% to 2.3%.

[0042] In some embodiments, the oil content of the solid phase remaining after chemical thermal washing of the oil sludge is ≤5%.

[0043] The oil content can be 1%, 2%, 3%, 4%, 5%, etc.

[0044] S2, mixing the pretreated oil sludge thermal cracking residue and the remaining solid phase of oil sludge chemical heat washing to obtain a mixture, wherein the mass fraction of the oil sludge thermal cracking residue in the mixture is 20% to 50%;

[0045] The positive effect of controlling the mass fraction of the sludge thermal cracking residue to 20% to 50% is that if the mass fraction is too small, the fixed amount of the sludge thermal cracking residue is too small, and the cracking residue cannot be efficiently processed; if the mass fraction is too large, the formability of the mixture and the binder is poor, and high-strength ceramsite cannot be obtained. The mass fraction of the sludge thermal cracking residue can be 20%, 30%, 40%, 50%, etc.

[0046] S3, mixing the mixture with a binder according to a set mass ratio, and then granulating and aging to obtain raw material balls;

[0047] In some embodiments, the binder is water and the like.

[0048] In some embodiments, the mass ratio of the mixture to the binder is (2-3):1.

[0049] The mass ratio of the mixture to the binder can be 2:1, 2.2:1, 2.4:1, 2.8:1, 3:1, etc.

[0050] In some embodiments, the aging method includes: drying or natural drying.

[0051] S4, preheating and sintering the raw material balls, and obtaining high-strength ceramsite after cooling;

[0052] In some embodiments, the preheating temperature is 350° C. to 450° C., and the preheating time is 20 min to 40 min.

[0053] The preheating temperature can be 350°C, 370°C, 390°C, 410°C, 430°C, 450°C, etc., and the preheating time can be 20 min, 25 min, 30 min, 35 min, 40 min, etc.

[0054] In some embodiments, the sintering temperature is 1125° C. to 1175° C., and the sintering time is 10 min to 30 min;

[0055] The positive effect of controlling the sintering temperature to 1125℃~1175℃: if the temperature is too high, too much liquid phase will be produced, the ceramsite will be over-burned, causing the material to melt and deform, and the sintering effect will be poor; if the temperature is too low, the solid phase cannot react completely. The sintering temperature can be 1125℃, 1135℃, 1155℃, 1165℃, 1175℃, etc.

[0056] The positive effect of controlling the sintering time to 10min to 30min: if the time is too long, the liquid phase inside the ceramsite will increase, resulting in the interconnection of the controlled pores and poor sintering effect; if the temperature time is too short, the solid phase cannot react completely. The sintering time can be 10min, 15min, 20min, 25min, 30min, etc.

[0057] In some embodiments, when the mass fraction of the sludge thermal cracking residue in the mixture is 50%, the sintering process conditions include: if the sintering temperature is 1150° C., the sintering time is 30 minutes; if the sintering temperature is 1175° C., the sintering time is 20 minutes.

[0058] In some embodiments, when the mass fraction of the sludge thermal cracking residue in the mixture is 20%, the sintering process conditions include: if the sintering temperature is 1150° C., the sintering time is 20 minutes, and if the sintering temperature is 1175° C., the sintering time is 10 minutes.

[0059] The amount of sludge thermal cracking residue added is positively correlated with the sintering temperature and time. High-strength ceramsite with the best sintering effect can be obtained by changing the sintering temperature or time.

[0060] In a second aspect, the present application provides a high-strength ceramsite, which is prepared by the method described in any one of the embodiments of the first aspect, and the high-strength ceramsite includes the following mineral components in mass fractions: clay: 10.6% to 12.0%, quartz: 57.0% to 62.0%, potassium feldspar: 5.8% to 8.0%, plagioclase: 16.0% to 20.0, and hematite: 2.5% to 6.5%.

[0061] In some embodiments, the high-strength ceramsite satisfies at least one of the following properties: cylinder pressure strength ≥ 15.0 MPa, bulk density ≤ 1000 kg / m 3 The water absorption rate is 0.5% to 0.7%, and the particle diameter is 10mm to 20mm.

[0062] The prepared ceramsite meets the requirements for light aggregate in "Light Aggregate and Its Test Methods" (GB / T 17431.1-2010) and is a high-strength ceramsite. Its compressive strength is stronger than that of unburned bricks and red bricks, and it can replace sand and gravel as roadbed materials or building materials. The cylinder compressive strength can be 15.0MPa, 19.0MPa, 21.0MPa, 25.0MPa, etc., and the bulk density can be 800kg / m 3 、850kg / m 3 , 900kg / m 3 , 950kg / m 3 , 1000kg / m 3 The water absorption rate can be 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, etc., and the particle size diameter can be 10mm, 12mm, 14mm, 18mm, 20mm, etc.

[0063] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0064] The properties and pretreatment methods of the oil sludge thermal cracking residue and the chemical heat washing residual solid phase in Example 1 and Example 2 are as follows.

[0065] The raw material pyrolysis residue was collected from a sludge pyrolysis treatment process in Liaohe Oilfield, and its main raw material was ground sludge containing impurities. The residue is black fly ash powder and a small amount of black lumps. After drying, it is sieved through a 100-mesh screen for use. The mass fraction of the elements in the sludge pyrolysis residue is: C: 30.1%~52.7%, O: 4.9%~32.6%, Si: 7.6%~29.8%, Al: 2.9%~8.1%. The mass fraction of the mineral components in the sludge pyrolysis residue is: clay 13.0%, quartz 54.8%, potassium feldspar 7.9%, plagioclase 20.8%, calcite 2.0%, pyrite 1.5%, amorphous 17.2%.

[0066] The residual solid phase of chemical heat washing was collected from a certain oil sludge chemical heat washing process in Liaohe Oilfield, and its main raw material was ground oil sludge. The residual solid phase of chemical heat washing was brown-yellow and silty, with a water content of 17.63% and an oil content of less than 2%. It was ground after drying at 105°C and passed through a 100-mesh sieve for later use. The mineral composition of the residual solid phase of chemical heat washing was as follows: clay 5.7%, quartz 64.9%, potassium feldspar 9.9%, plagioclase 18.6%, and calcite 1.3%.

[0067] Example 1

[0068] S11, mixing the oil sludge thermal cracking residue and the chemical thermal washing remaining solid phase in a ratio of 1:1 to obtain a mixture;

[0069] S21. Take an appropriate amount of water and add it to the mixture. The mass ratio of the mixture to water is 2.5:1. Stir evenly. The amount of water can be adjusted appropriately according to the actual situation. Granulate to make the particle diameter of the ceramsite about 10mm to 20mm. The balled raw material is dried in an electric heating blast drying oven at 105℃ for 5h.

[0070] S41. Preheat the raw material balls in a box-type resistance furnace at 400°C for 30 minutes, then sinter at 1175°C for 20 minutes, and obtain the ceramsite product after cooling.

[0071] The cylinder compressive strength of the high-strength ceramsite obtained in this example is 24.53 MPa and the bulk density is 858 kg / m 3 The water absorption rate is 0.59%. It meets the requirements of light aggregate in the prepared ceramsite "Light Aggregate and Its Test Methods" (GB / T 17431.1-2010) and is a high-strength ceramsite.

[0072] The mineral composition of sintered ceramsite is 11.6% clay, 58.9% quartz, 6.8% potassium feldspar, 17.9% plagioclase and 4.8% hematite.

[0073] The heavy metal leaching concentrations of high-strength expanded clay are: arsenic < 0.10μg / L, selenium < 0.10μg / L, mercury 11.69μg / L, lead 0.22mg / L, zinc 0.13mg / L, cadmium < 0.05mg / L, nickel < 0.03mg / L, copper < 0.02mg / L, total chromium < 0.03mg / L, silver < 0.2μg / L, barium < 2.5μg / L, hexavalent chromium 0.018mg / L, which are lower than the concentration limits of hazardous components in the leachate specified in the "Identification Standard for Hazardous Wastes - Identification of Leaching Toxicity" (GB 5085.3-2007).

[0074] Example 2

[0075] S11, mixing the oil sludge thermal cracking residue and the chemical thermal washing remaining solid phase in a ratio of 1:1 to obtain a mixture;

[0076] S21. Take an appropriate amount of water and add it to the mixture. The mass ratio of the mixture to water is 2.5:1. Stir evenly. The amount of water can be adjusted appropriately according to the actual situation. Granulate to make the particle diameter of the ceramsite about 10mm to 20mm. The balled raw material is dried in an electric heating blast drying oven at 105℃ for 5h.

[0077] S41. Preheat the raw material balls in a box-type resistance furnace at 400°C for 30 minutes, then sinter them at 1150°C for 30 minutes, and obtain the ceramsite product after cooling.

[0078] The cylinder compressive strength of the high-strength ceramsite obtained in this example is 23.51 MPa and the bulk density is 991.43 kg / m 3 The water absorption rate is 0.73%. It meets the requirements of light aggregate in the prepared ceramsite "Light Aggregate and Its Test Methods" (GB / T 17431.1-2010) and is a high-strength ceramsite.

[0079] The mineral composition of sintered ceramsite is 11.4% clay, 60.3% quartz, 4.3% potassium feldspar, 19.1% plagioclase and 4.9% hematite.

[0080] The heavy metal leaching concentrations of high-strength expanded clay are: arsenic 41.7μg / L, selenium <0.10μg / L, mercury 11.69μg / L, lead <0.06mg / L, zinc <0.06mg / L, cadmium <0.05mg / L, nickel <0.03mg / L, copper <0.02mg / L, total chromium <0.03mg / L, silver <0.2μg / L, barium <2.5μg / L, hexavalent chromium 0.015mg / L, which are lower than the concentration limits of hazardous components in the leachate specified in the "Identification Standard for Hazardous Wastes - Identification of Leaching Toxicity" (GB 5085.3-2007).

[0081] Attached Figure 2 , 3 Detailed description: Figure 2 , 3 It can be seen that there are more pores in the ceramsite. This is because the carbon content in the thermal cracking residue is high, and CO or CO is generated during the high-temperature reaction during the ceramsite sintering process. 2 The gases in the clay form internal pores, thus reducing the bulk density of the ceramsite.

[0082] In addition, one or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:

[0083] In the embodiments of the present invention, the leaching concentration of heavy metals in the ceramsite is lower than the concentration limit of hazardous components in the leachate specified in the "Identification Standard for Hazardous Wastes - Identification of Leaching Toxicity" (GB 5085.3-2007).

[0084] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A method for preparing high-strength ceramsite using oil sludge-based solid waste, characterized in that: The method comprises: The oil sludge thermal cracking residue and the oil sludge chemical heat washing residual solid phase are pretreated respectively; The pre-treated oil sludge thermal cracking residue and the remaining solid phase of oil sludge chemical heat washing are mixed to obtain a mixture, wherein the mass fraction of the oil sludge thermal cracking residue in the mixture is 20% to 50%; The mixture is mixed with a binder according to a set mass ratio, and then granulated and aged to obtain raw material balls; The raw material balls are preheated and sintered, and high-strength ceramsite is obtained after cooling, wherein the sintering temperature is 1125° C. to 1175° C., and the sintering time is 10 min to 30 min; The oil sludge thermal cracking residue comprises the following elemental components in mass fractions: C: 30.1% to 52.7%, O: 4.9% to 34.6%, Si: 7.6% to 29.8%, and Al: 2.9% to 8.1%.

2. The method according to claim 1, characterized in that When the mass fraction of the sludge thermal cracking residue in the mixture is 50%, the process conditions of the sintering include: if the sintering temperature is 1150° C., the sintering time is 30 minutes; if the sintering temperature is 1175° C., the sintering time is 20 minutes.

3. The method according to claim 1, characterized in that When the mass fraction of the sludge thermal cracking residue in the mixture is 20%, the process conditions of the sintering include: if the sintering temperature is 1150° C., the sintering time is 20 minutes; if the sintering temperature is 1175° C., the sintering time is 10 minutes.

4. The method according to claim 1, characterized in that: The oil sludge thermal cracking residue comprises the following mineral components in mass fractions: clay: 11.0% to 15.0%, quartz: 46.0% to 56.0%, potassium feldspar: 5.9% to 9.9%, plagioclase: 15.0% to 21.0%, calcite: 1.0% to 3.0%, pyrite: 0.5% to 2.5%, and amorphous: 10.2% to 18.2%.

5. The method according to claim 1, characterized in that The residual solid phase of the oil sludge chemical thermal washing comprises the following mineral components in mass fraction: clay: 4.7% to 7.0%, quartz: 60.9% to 68.9%, potassium feldspar: 7.9% to 12.2%, plagioclase: 15.6% to 21.0%, and calcite: 0.6% to 2.3%; the oil content of the residual solid phase of the oil sludge chemical thermal washing is ≤5%.

6. The method according to claim 1, characterized in that The set mass ratio is (2-3):

1.

7. The method according to claim 1, characterized in that The preheating temperature is 350° C. to 450° C., and the preheating time is 20 min to 40 min.

8. The method according to claim 1, characterized in that The aging method includes: drying or natural drying.

9. A high-strength ceramsite, characterized in that: The high-strength ceramsite is prepared by the method described in any one of claims 1 to 8, and comprises the following mineral components in mass fractions: clay: 10.6% to 12.0%, quartz: 57.0% to 62.0%, potassium feldspar: 5.8% to 8.0%, plagioclase: 16.0% to 20.0, and hematite: 2.5% to 6.5%.

10. The high-strength ceramsite according to claim 9, characterized in that: The high-strength ceramsite meets at least one of the following properties: cylinder pressure strength ≥ 15.0MPa, bulk density ≤ 1000kg / m 3 The water absorption rate is 0.5% to 0.7%, and the particle diameter is 10mm to 20mm.

Citation Information

Patent Citations

  • A method for preparing lightweight ceramsite by co-recycling oil sludge and solid waste.

    CN105906176B

  • Method for preparing building ceramsite by utilizing oil sludge and spent clay

    CN109305769A

  • Method for fixing heavy metals in oil sludge dry residues, porous ceramsite and application

    CN111196731A

  • Oil sludge ceramsite lightweight aggregate and preparation method thereof

    CN113003970A

  • Ceramsite prepared from residues generated in oil containing sludge pyrolysis and preparation method thereof

    CN109851323A